Maduración y fecundación de ovocitos bovinos in vitro : participación de las especies reactivas del oxígeno - Morado, Sergio Adrián (2015)
The role of reactive oxygen species (ROS) in the processes related with gametes and embryo in vitro culture and manipulation is still controversial. It has been proposed that an adecquate level of O2 - (superoxide anion) would be necessary during bovine oocyte in vitro maturation (IVM) in order to increase their developmental competence. In coincidence, a gradual increase in ROS levels has been observed in embryos developing\nfrom 2-cells until morula stage, which could depend on the metabolic changes that occur in the bovine embryo. On the other hand, certain studies have demonstrated the expression of genes which codify for antioxidant enzymes throughout the in vitro culture of cumulusoocyte\ncomplexes. These studies propose that the storage of antioxidants in the oocyte\nduring its growth and maturation (in the forms of mRNA or proteins) would be important for the future embryo to achieve developmental competence.\nThe apparent contradiction in some of the existing reports, together with the results obtained in previous studies in our laboratory, suggest the need to develop further research to determine if ROS play an important role in the meiotic progress and\ncytoplasmic maturation of the oocyte. Therefore, the main aim of this work was to\ndetermine the possible fluctuation in ROS production during in vitro maturation and\nactivation of bovine oocytes and its relation with key events of both processes.\nIn this study, ROS production proved to be fluctuating during the whole process of IVM. A significant difference was observed in ROS generation between 2 and 18h, which could correspond to a period of time which demands a high energy production in the\nrespiratory chain for protein synthesis during the preparatory stages of IVM key events. With respect to oocyte activation, we observed distinct metabolic patterns between non-activated, sperm mediated and parthenogenetically activated oocytes. The different behaviour as regards ROS levels and oxidative activity in sperm mediated and parthenogenetic activation could be related to the difference in the Ca+2 waves which has been documented between both types of activation. The unique Ca+2 wave triggered by parthenogenetic activation would not be efficient to stimulate mitochondria consistently,\nbeing therefore responsible for the lower developmental competence reported in this type of activation. Modulating reduced gluthatione (GSH) levels we observed that although GSH role as antioxidant could be compensated by other components of the oocyte´s antioxidant system, its participation in the maintenance of the meiotic spindle morphology would be essential for maturation.\nWhen we analysed the effect of the modulation of nitric oxide (NO) endogenous\nand exogenous levels on ROS production during IVM, the addition of NO donors proved to be deleterious for maturation regardless of the variations in ROS levels. Therefore, we could conclude that an increase in NO levels in the oocyte could impair meiotic\nprogression both due to the formation of peroxynitrite or due to the inhibition of the\nmitogen activated protein kinase and the maturation promoting factor, which are involved in intracellular signal transduction systems that play a role in maturation. The inhibition of the NADPH oxidase by the addition of an enzymatic inhibitor to IVM medium showed that the inhibition of the enzyme would not generate changes in ROS\nlevels, but the consequent decrease in the generation of O2 - would affect embryo\ncleavage rate, probably due to the participation of this ROS in signalling systems involved in the process of activation. The addition of enzymatic systems to modulate hydrogen peroxide (H2O2) and O2 - levels showed that although the addition of H2O2 and O2\n?- generating systems could be deleterious for oocyte quality, the use of scavengers would alter maturation by interfering\nwith intracelular signaling systems. These results would demonstrate that certain ROS levels are necessary for bovine oocyte maturation, probably due to their participation in\nsignalling systems of the process. Using modulators of the mitochondrial respiratory chain activity we determined that\nthe ATP produced in the mitochondria would be especially important at 12 h, a period of time in which there is a high metabolic activity due to an intense protein synthesis\ncoinciding with the metaphase I ? metaphase II transition. In conclusion, we determined significant fluctuations in ROS levels during the in vitro maturation and activation of bovine oocytes. The observed variations are related to\nkey events of both processes and are relevant to increase the knowledge regarding the\ndevelopmental competence of oocytes and early embryos. These results suggest that it\nwould be important to lead future experiments in order to elucidate if the fluctuations\nobserved only respond to variations in metabolic activity or if certain ROS also play a role in intracellular regulatory or signalling systems. Moreover, further studies on the metabolic\ncontrol of parthenogenetic activation could contribute to improve the performance of\nparthenogentic embryos in different biotechnological applications such as nuclear transfer, cloning and trans genesis.